The association between sugar-sweetened beverage consumption, muscle strength, and psychological symptoms among Chinese adolescents: a multicenter cross-sectional survey - Zhou, Yanjie; Xue, Chunhua; Ahmat, Gulnur; Lou, Huijuan; Liu, Yun; Ma, Li (Frontiers in Nutrition, 2025)
BackgroundThe prevalence of psychological symptoms in adolescents has been increasing and has become an important public health issue of concern to countries around the world. However, no studies have been conducted on the association between sugar-sweetened beverage (SSB) consumption, muscle strength, and psychological symptoms in Chinese adolescents. The present study may provide theoretical support and assistance for the prevention and intervention of psychological symptoms in Chinese adolescents.MethodsIn this study, 42,832 adolescents aged 12–17 years in mainland China were assessed cross-sectionally for SSB consumption, standing long jump reflecting muscle strength, psychological symptoms, and related covariates using a three-stage stratified whole-cluster random sampling method. The methods of univariate analysis, logistic regression analysis, and binary Logistic regression analysis with a generalized linear model were used for the analysis.ResultsThe prevalence of psychological symptoms among Chinese adolescents aged 12–17 years was 21.2%; the prevalence of boys (22.0%) was higher than that of girls (20.3%), and the difference was statistically significant (χ2 = 18.320, p < 0.001). The percentage of adolescents with SSB consumption frequency of ≥4 times/week was 14.6%. The mean standing long jump of adolescents was (186.80 ± 33.16) cm. Binary Logistic regression analysis with the generalized linear model was performed with the presence of psychological symptoms in adolescents as the dependent variable and different combinations of SSB consumption and standing long jump quartile as independent variables. Overall results showed that the risk of psychological symptoms among adolescents in the SSB consumption ≥4 times/week and standing long jump quartile Q1 group was higher than that of adolescents in the SSB consumption ≤1 times/week and standing long jump quartile Q4 group adolescents by 2.05 times (95% CI: 1.76–2.38) (p < 0.001).ConclusionThere is an association between SSB consumption, muscle strength, and psychological symptoms in Chinese adolescents. Effective reduction of SSB consumption and improvement of muscle strength may be an effective way to reduce psychological symptoms. The effects of SSB consumption and muscle strength should be emphasized in the prevention and intervention of adolescents’ psychological symptoms in the future.